A 3D Decentralized Guidance and Control System for a Swarm of Multi-Copters. Issue 1 (July 2017) - Tartaglione, Gaetano; Ariola, Marco; D'Amato, Egidio; Rossi, Pierluigi Salvo
Abstract: In this paper we present a decentralized real-time system for the guidance and control of a swarm of multi-copters in a 3D environment. A hierarchical architecture is proposed for trajectory planning and tracking based on the control of the multi-copter attitude and velocity. The guidance module generates the reference trajectory as a sequence of way-points, obtained as solution to a constrained optimization problem. The tracking trajectory module is based on a distributed and robust Model Predictive Control (MPC) technique. Finally, a cascaded PID controller is used for attitude and velocity control. To test the proposed scheme, we consider a cooperative load transport problem in which a suspended load is linked by wires to the multi-copters. Numerical simulations of realistic scenarios are presented. The results are encouraging, thus making the proposed system an appealing candidate for a wide range of applications.